To Forgive but not Forget? On the Relationship between Recognition and Reconciliation in Indigenous-settler Australian Relations - Qian, Ng Qian (Itinerari, 2023)
What is the relationship between recognition and reconciliation? I argue that reconciliation undermines recognition’s promise of eventual attainment of freedom for all, even as it is crucial to the project of recognition. As this crucial relationship has been undertheorized, this paper hopes to spark new conversations within recognition theory. I discuss the reconciliation between Indigenous Australian peoples and the settler-colonial state, focusing on the pivotal 2008 apology for the “Stolen Generations” and more recent proposal of Makarrata. Drawing on literature on anger, forgiveness and psychoanalysis by Agnes Callard, Jacques Derrida and Paul Muldoon, I propose four criteria for a proper apology for reconciliation. Applying these criteria to the 2008 Apology by then Prime Minister Kevin Rudd, I argue that the apology is inadequate, and further that an apology can never be an adequate mode of reconciliation. I end by considering prospects of alternative forms of reconciliation.